A single dose of beetroot juice enhances cycling performance in simulated altitude - Muggeridge, D. J.; Howe, C. C. F.; Spendiff, O.; Pedlar, C.; James, P. E.; Easton, C. (Medicine & Science in Sports & Exercise, 2014)
Introduction: Increasing nitric oxide bioavailability via supplementation with nitrate-rich beetroot juice (BR) has been shown to attenuate the negative effect of hypoxia on peripheral oxygen saturation and exercise tolerance.